Perlindungan Hukum Hak Pilih Penyandang Disabilitas Mental dalam Pemilihan Umum di Indonesia - Kartika Sari, Fitri; Kusaimah, Kusaimah; Salman, Salman (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2023)
People with mental disorders being involved in the 2024 election is an interesting topic of discussion. In this context, there are many pros and cons. The question arises as to whether those with mental disorders have the right to vote. This is interesting to research and review. This article aims to analyze the right to vote for people with mental disabilities in the 2024 elections. Apart from that, this research also analyzes the Constitutional Court decision Number 135/PUU-XIII/2015. This research departs from a normative study with a statute approach. This approach is used to view and analyze legal aspects related to the problems in this research. This article argues that the legal regulation of the right to vote in elections for disabled people with mental disorders is regulated in Article 4 paragraph (2) letter b and Article 4 paragraph (3) General Election Commission Regulation (PKPU) Number 11 of 2018 concerning the Compilation of the Domestic Voter List. The General Election Organizers were then revised with PKPU 37 of 2018, which deleted the provisions of Article 4 paragraph (2) letter b and Article 4 paragraph 3 in order to comply with the decision of the Constitutional Court. People with persistent mental or memory disorders do not have the right to vote in elections.